MAMMAL DIVERSITY IN THE PUTUMAYO-NAPO-AMAZONAS INTERFLUVIUM, NORTH OF THE PERUVIAN AMAZON - RIVEROS, María S. (2020)
Mammals maintain the structure of the forest and are important as a source of protein and economic income for Amazonian people. To determine the diversity of large and medium bodied mammals (excluding bats and small rodents) in the Putumayo-Napo-Amazonas interfluvium, 1908.1 km of linear transects were walked recording tracks and sightings, 146 camera traps were deployed for a total of 977 camera days, and burrows were searched for on 118,4 km of transects. In addition, species recorded were collected from 13 publications between 2004 and 2020. Diversity was taken as the species richness, while the expected richness was estimated with Chao 1 and the similarity between habitats was analyzed with the Morisita index. Species richness was high; 56 species from 26 families and 9 orders were recorded, and it was similar in low hills, high terraces, middle terraces and mixed palm swamps, but it was very low in peatland pole forest and riverine forest. The middle terrace and mixed palm swamps were very similar according to the Morisita index, as were the high terrace and low hill. The primates Leontocebus nigricollis, Pithecia hirsuta, Cheracebus lucifer, and Lagothrix lagothricha lagothricha are restricted to this interfluvium. The most threatened species present were Pteronura brasiliensis and L. lagothricha. The most frequent anthropogenic threats were overhunting, selective logging and deforestation. This watershed has a high diversity of mammals and healthy populations of game animals with the potential for sustainable use to benefit native communities and mitigate threats to the area from unsustainable use.